2011
DOI: 10.1111/j.1743-6109.2011.02417.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Effects of a Low-energy Diet and a High-protein Low-fat Diet on Sexual and Endothelial Function, Urinary Tract Symptoms, and Inflammation in Obese Diabetic Men

Abstract: Introduction Abdominal obesity and type 2 diabetes mellitus are associated with sexual and endothelial dysfunction, lower urinary tract symptoms (LUTS), and chronic systemic inflammation. Aim To determine the effects of diet-induced weight loss and maintenance on sexual and endothelial function, LUTS, and inflammatory markers in obese diabetic men. Main Outcome Measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
154
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 33 publications
7
154
3
Order By: Relevance
“…Few randomized clinical studies have specifically evaluated the impact of diet and physical activity on testosterone levels in obese men. The results of these studies are essentially conflicting: some of them showed an increase of testosterone (26,27,28,29,30,31,32,33,34), others showed no change (35,36,37,38,39), and one small study has shown even a decrease in testosterone levels (40). Similarly, in the last 10 years, several trials have evaluated the impact of bariatric surgery on testosterone levels in men generally, showing an increase in testosterone levels (41,42,43,44,45,46,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…Few randomized clinical studies have specifically evaluated the impact of diet and physical activity on testosterone levels in obese men. The results of these studies are essentially conflicting: some of them showed an increase of testosterone (26,27,28,29,30,31,32,33,34), others showed no change (35,36,37,38,39), and one small study has shown even a decrease in testosterone levels (40). Similarly, in the last 10 years, several trials have evaluated the impact of bariatric surgery on testosterone levels in men generally, showing an increase in testosterone levels (41,42,43,44,45,46,47,48).…”
Section: Introductionmentioning
confidence: 99%
“…The pilot trial conducted by Pavlou et al (1989) and three other trials (Benassi-Evans et al, 2009;Khoo et al, 2011;Wycherley et al, 2012) examined varying the protein, carbohydrate, and fat proportions of reducing diets, or examined a more stringent initial calorie prescription of 900 kcal for 8 weeks followed by a 600 kcal/day deficit to 600 kcal/day deficit alone. None of the trials identified significant differences between the different dietary approaches after 12 months.…”
Section: Types Of Calorie Reducing Diet Comparedmentioning
confidence: 99%
“…Of these, 21 reports (14 RCTs [Benassi-Evans, Clifton, Noakes, Keogh, & Fenech, 2009;Borg, Kukkonen-Harjula, Fogelholm, & Pasanen, 2002;Esposito et al, 2004;Hunt et al, 2014;Jeffery, Gerber, Rosenthal, & Lindquist, 1983;Khoo et al, 2011;King, Frey-Hewitt, Dreon, & Wood, 1989;Morgan, Lubans, Collins, Warren, & Callister, 2011;Patrick et al, 2011;Pavlou, Krey, & Steffee, 1989;Van Aggel-Leijssen, Saris, Hul, & van Baak, 2001;Wood et al, 1988;Wycherley, Brinkworth, Clifton, & Noakes, 2012] with seven linked reports [Collins et al, 2013;Fortmann, Haskell, & Wood, 1988; Jeffery, BjornsonBenson, Rosenthal, Lindquist, & Johnson, 1984;Kukkonen-Harjula, Borg, Nenonen, & Fogelholm, 2005; Lejeune, Aggel-Leijssen, van Baak, & WesterterpPlantenga, 2003;Lutze et al, 2013; Multiple Risk Factor Intervention Trial Research Group, 1982; Van AggelLeijssen, Saris, Hul, & van-Baak, 2002]) were eligible for inclusion. Details of the flow chart for the results of the literature search and a description of all the included trials are provided in Appendices C and D.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As visceral adiposity and insulin resistance are associated with the production of inflammatory cytokines and with the aromatization of testosterone into estradiol in the adipose tissue, weight loss leads to the release of pituitary gonadotropin and to the production of testicular androgens, in turn improving the sexual function. The strong points in the study are the comprehensive evaluations, parallel dietetic approaches, and relatively long duration [26].…”
Section: Low-energy Low-fat High-protein Dietmentioning
confidence: 99%